Randomly amplified polymorphic-DNA analysis for detecting genotoxic effects of Boron on maize (Zea mays L.). (August 2015) - Sakcali, M Serdal; Kekec, Guzin; Uzonur, Irem; Alpsoy, Lokman; Tombuloglu, Huseyin
This study was carried out to investigate the genotoxic effect of boron (B) on maize using randomly amplified polymorphic DNA (RAPD) method. Experimental design was conducted under 0, 5, 10, 25, 50, 100, 125, and 150 ppm B exposures, and physiological changes have revealed a sharp decrease in root growth rates from 28% to 85%, starting from 25 ppm to 150 ppm, respectively. RAPD-polymerase chain reaction (PCR) analysis shows that DNA alterations are clearly observed from beginning to 100 ppm. B-induced inhibition in root growth had a positive correlation with DNA alterations. Total soluble protein, root and stem lengths, and B content analysis in root and leaves encourage these results as a consequence. These preliminary findings reveal that B causes chromosomal aberration and genotoxic effects on maize. Meanwhile, usage of RAPD-PCR technique is a suitable biomarker to detect genotoxic effect of B on maize and other crops for the future.